Perbandingan Pengomposan Metode Karung Goni Dengan Pengomposan Di Atas Tanah Pada Sistem Aerobik - Purwiningsih, Dwi Wahyu (Jurnal Kesehatan Poltekkes Ternate, 2017)
Abstract Background: Garbage is still a problem in the cities in Indonesia is no exception in the city of Ternate, waste generation generated by the people of Ternate town that is transported to the landfill is 226 m3 / day, with the level of service 57% of the total community of Ternate CPM, 2015). Good waste management alternatives to deal with this problem one of them by using appropriate technology. One of the appropriate technology that can be applied is the use of composting media in the form of burlap sacks. Benefits of Research: test the theory of composting by using various media for aerobic composting. Research location: in Environmental Health Department of Poltekkes Ternate. Research Method: This type of experimental research using Posstest Only Control Design design. Processing and presentation of data in this study is the amount of compost produced from the composting process is weighed and differentiated according to media type and MOL then presented in table form and narrated. Research Result: Demonstrate the most compost-producing medium is the burlap sack with the addition of MOL Tape Ubi and the least is by ground composting with the addition of MOL Pineapple, the time used in the composting process for 20 days. Conclusions: The average number of the most widely produced compost is randomly sacked with MOL Tape Ubi, MOL Terasi MOL Pineapple and control.   Keywords: Garbage, Composting, Sackbox Media